BALI PIGS PREFERENCE AS RAW MATERIALS FOR SUCKLING PIG - SUKANATA I W.; B. R. T. PUTRI; SUCIANI . (Majalah Ilmiah Peternakan, 2018)
This study aims at observing the main attributes of bali pigs that prefer as a raw material suckling pig producer.Farmers have to know this thing in order to increase consumer satisfaction and their loyality. The data usedinterview and observation as primary data collected to fifty producers of suckling pig which is located in Bali. Theywere interviewed using questionnaires and analyzed with chi square and multiatribut Fishbein analysis. It showedthat preferences of producers based on attributes of color, gender, body size and body condition significantly differwithin 95% level of interest. Bali pig attributes that preferred by the producer as a raw material of roasted pig isbali pig with balck colour, sex of male, 10 up to 15 kg of body weight and fat body condition. The bali pig attributesconsidered by the producer in making decision to buy from the most consideration to the minimum such as bodysize, body condition, gender, and color. Body condition attribute was considered to be less satisfying for producersindicated with satisfaction score 2.9 from the maximum score of 5. So, it is important that farmers should payattention to these attributes in the future.